A Technical Guide to Palliative Ablation of Recurrent Cancers in the Deep Spaces of the Suprahyoid Neck - Hui, Terrence Chi Hong; Lim, Ming Yann; Karandikar, Amit Anand; Loke, Siu Cheng; Pua, Uei (Seminars in Interventional Radiology, 2022)
Treatment options for patients with recurrent head and neck cancer, whether locoregional recurrence of previously treated head and neck cancer or secondary primary malignancy, are limited. Percutaneous ablation is a minimally invasive procedure that can be used with palliative intent in the head and neck to achieve symptomatic relief and local tumor control, potentially fulfilling treatment gaps of current standard of care options. Image guidance is key when navigating the deep spaces of the neck with special attention paid to critical structures within the carotid sheath. This review article provides an overview and highlights the important nuances of performing percutaneous ablations in the head and neck. It covers general principles, ablative modalities, image guidance, procedural technique, expected outcomes, and possible complications.
Keywords: recurrent head and neck cancer; interventional radiology; cryoablation; cryoneurolysis; percutaneous thermal ablation